Fungal contamination in elderly care center and sick building syndrome / Mohamad Ihsan Anuar - Anuar, Mohamad Ihsan (2018)
Fungi is ubiquitous as it can be found anywhere worldwide and poses serious health threat to public health, with favourable condition such as temperature and carbon dioxide that inhibit fungal growth and contributes to occurrence of Sick Building Syndrome (SBS). Sick Building Syndrome is a situation where occupants experienced acute health effect which is linked to amount of time spent in the building. This study is conducted at elderly care centre to identify environmental factors of fungal contamination and environmental condition that contribute to Sick Building Syndrome, to evaluate relationship between indoor air quality and fungal contamination in indoor environment and to identify genus of common indoor fungi in indoor air environment. Methods used are environmental monitoring and checklist of building inspection. Indoor air quality parameter measured are temperature and carbon dioxide by using Q-Trak. Total colony count of fungi represent fungi colony measured using Potato Dextrose Agar (PDA) with open plate method. Checklist for building inspection used to determine environmental condition of building and identification of fungi determined by using culture characteristics. For both ECC, average temperature level exceeded the limit by ICOP which are 29 xiii 0 C and average carbon dioxide level are 488.38 ppm and 470.67 ppm respectively. Average total colony count of fungi isolated in both ECC are 170 cfu/m 3 and 183 cfu/m 3 respectively. Descriptive statistics is used to determine mean difference between each parameter measured and Pearson’s correlation is used to determine relationship between temperature and carbon dioxide with fungal growth and there is strong correlation between carbon dioxide and fungal growth. Three genera identified in this study are common fungi in indoor environment which is Aspergillus sp. Cladosporium sp., and Penicillium sp. This study concludes that changes in indoor air quality influence the growth of fungi and SBS. This study suggests further evaluation on indoor air quality, fungal growth and sick building syndrome, and changes should be made to improve the quality of life among elders in elderly care centre.